Stars in their eyes - Walton, Jessica (Graphix, an imprint of Scholastic Inc., 2023)
Maisie is on her way to her first fancon and she can't wait to meet her idol, an action star who had an above-the-knee amputation, just like Maisie. But then she meets Ollie. Ollie is a cute volunteer working the show, and they geek out about nerd culture, just as much as Maisie does. After spending the day together, Maisie notices feelings for Ollie that she's never had before. Could Ollie feel the same way?